New trends in haemostasis: coagulation proteins, endothelium, and tissue factors - Harenberg, Job; Heene, Dieter L.; Stehle, Gerd; Schettler, Gotthard (Sitzungsberichte der Heidelberger Akademie der Wissenschaften, Mathematisch-Naturwissenschaftliche Klasse, 1990)
To give an update in the field of haemostasis scientists and clinicians fromoverseas and European countries met to dis- cuss the new trends in pathophysiology and clinical impli- cations. This book is devoted to the interactions of endo- thelial functions, tissue factors, coagulation inhibitors and haemostasis as well as detection and prophylaxis of thromboembolism. Data are presented of significant new re- search work on molecular and clinical approaches to diseases in haemostasis